Beyond COVID-19, the case for collecting, analysing and using sex-disaggregated data and gendered data to inform outbreak response: a scoping review - Simone E Carter; Shirin Heidari; Leah Zilversmit Pao; Marie-Amelie Degail; Marie Meudec; McKinzie Gales; Emelie Love Yonally Phillips; Christine Dubray; Clara Rodriguez Ribas Elizalde; M Ruby Siddiqui (BMJ Global Health)
Introduction Understanding sex and gender differences during outbreaks is critical to delivering an effective response. Although recommendations and minimum requirements exist, the incorporation of sex-disaggregated data and gender analysis into outbreak analytics and response for informed decision-making remains infrequent. A scoping review was conducted to provide an overview of the extent of sex-disaggregated data and gender analysis in outbreak response within low- and middle-income countries (LMICs).Methods Five databases were searched for peer-reviewed literature examining sex- and gender-specific outcomes for communicable disease outbreaks published in English between 1 January 2012 and 12 April 2022. An adapted version of the WHO’s Gender Analysis Matrix was used to synthesise evidence, which was then mapped across four phases of the outbreak timeline: prevention, detection, treatment/management and recovery.Results 71 articles met inclusion criteria and were included in this review. Sex-, gender-, and pregnancy-related disparities were identified throughout all four phases of the outbreak timeline. These disparities encompassed a wide range of risk factors for disease, vulnerability, access to and use of services, health-seeking behaviour, healthcare options, as well as experiences in healthcare settings and health and social outcomes and consequences.Conclusion Significant gender-evidence gaps remain in outbreak response. Evidence that is available illustrates that sex and gender disparities in outbreaks vary by disease, setting and population, and these differences play significant roles in shaping outbreak dynamics. As such, failing to collect, analyse or use sex-disaggregated data and gendered data during outbreaks results in less effective responses, differential adverse health outcomes, increased vulnerability among certain groups and insufficient evidence for effective prevention and response efforts. Systematic sex- and gender-based analyses to ensure gender-responsive outbreak prevention, detection, treatment/management and recovery are urgently needed.